Dynamic Mechanical Behaviors of Desert Sand Concrete (DSC) after Different Temperatures - Zhang, Minghu; Liu, Haifeng; Sun, Shuai; Chen, Xiaolong; Doh, Shu Ing (MDPI, 2019)
In the building domain, the non-renewable resource of sand is widely used to produce concrete and mortar. The sand production has been estimated to be more than 10 billion tons with a total of 1.2 billion tons used in concrete in the last decade, which causes the gradual reduction of available building materials and impacts the environment. Since there are abundant desert sand resources in northwestern China, it would be viable to utilize desert sand as an alternative material for concrete production. In this study, an investigation of dynamic mechanical behaviors of desert sand concrete (DSC) was conducted. Various desert sand replacement ratios (0–100%) were used to replace the equivalent hill sand as fine aggregate. Experimental results showed that strain rate had a strong effect on the dynamic mechanical behaviors of DSC. The compressive strength (at room temperature) and flexural strength (after elevated temperature) increased with desert sand replacement ratio (DSRR) with the optimum replacement ratio of 40%, which was because the increase of DSRR improved the compaction of DSC. However, the effect of the low strength of desert sand was higher than that of the compaction when the DSSR exceeded 40%, so both strength values generally decreased with the increase of DSRR. Moreover, the dynamic constitutive model of DSC at room temperature was established on the basis of a nonlinear visco–elastic constitutive model (ZWT model), which can predict the stress–strain curves of DSC.